Influence of CuO nanoparticles on photosystem II structural stability and functional activity of corn (Zea mays L.) under drought stress - Shakeel Ahmad; Abdul Razzaq; Ismat Umar; Binish Khaliq; Muhammad Javed; Muhammad Iqbal (International Journal of Applied and Experimental Biology)
Photoinhibition and photooxidation of photosystem II (PSII) is one of the key damages caused by drought stress. The present study aimed to assess whether or not foliar application of copper oxide nanoparticles (CuO NPs) is effective in promoting PSII stability and activity in corn plants under drought stress. Three-week old plants of corn were subjected to drought stress and varying levels of CuO nano-particles (0, 25, 50, and 100 mM) of the rooting medium. In this study, the effects of foliar application of copper oxide nanoparticles were assessed on growth, plant water status, nutrient uptake and structural stability of photosystem II of drought stressed corn plants. Drought stress impeded overall growth of the corn plants by reducing leaf relative water content, water potential, chlorophyll a content, and accumulation of K+ in plant leaves and roots. Exogenous application of 25 mM CuO NPs significantly enhanced the growth of corn. Exogenous application of CuO NPs improved the dry biomass and length of roots of the corn plants under drought stress. Although the application of nano-particles did not change leaf photosynthetic pigments, relative water content, K+ accumulation, it enhanced the accumulation of K+ in roots. Drought stress did not affect the structural stability of PSII, but it reduced its activity (performance index, PIABS) due to changes in the reaction center density and the biochemical reaction efficiency or electron transport capability. Exogenous application of CuO NPs improved PIABS due to increase in active reaction center density and electron transport efficiency. However, 100 mM CuO NPs application caused PSII damage at the donor end and reduced active reaction center density in the corn plants under both normal and drought stress conditions. The present findings provide a baseline information that foliar application of CuO-nanoparticles in low concentrations can improve the growth of corn by improving accumulation of K+ and increasing PSII activity. Further research is required to explore its effect on cellular redox balance and activities of PSII and PSI, and optimum dose of CuO-nanoparticles for developing formulations for their commercial applications in farmers’ fields.